Sequential evaluation of DNA damage in patients with head and neck carcinoma receiving radiotherapy - Siva Kumar M; Ariyanachi K; Vidhya Meena S; Lakshmi Jyothi Tadi; Sai Sailesh Kumar Goothy (Asian Journal of Medical Sciences, 2022)
Background: Head and neck cancers account for about 30% of all cancers in India. Studies showed that there is an increased primary DNA damage even before the commencement of any modality of treatment in cancer patients which is further increased by the treatment. Chemo-radiation induced DNA damage is not repaired so effectively in patients with carcinoma which might pave way for secondary carcinoma. Aims and Objectives: The aim of this study was to assess the degree of DNA damage by comet assay technique in patients with head and neck carcinoma receiving radiotherapy. The degree of DNA damage was compared according to the age, gender, and associated risk factors of the patients. Materials and Methods: 35 patients with Stages II, III, and IVA, histopathologically confirmed Squamous cell carcinoma of head and neck with Karnofsky Performance Status >70 attending radiotherapy OPD for treatment were included in this study.1 ml of heparinized blood was collected from the study participants during various doses of radiation treatment. All the samples were processed immediately and analyzed for DNA damage by single cell gel electrophoresis assay - Comet assay technique. Results: The comet length parameter, head diameter, and tail length were found to be increased when compared to baseline sample. The percentage of DNA in head parameter of post-RT sample was decreased when compared to baseline sample All these findings are indicative of DNA damage following radiotherapy. Conclusion: Patients with locally advanced head and neck carcinoma following radiotherapy showed a sequential increase in the DNA damage. The co-existing risk factors and old age may increase the baseline DNA damage in the patients with head and neck cancers.